CURRENT ASPECTS OF PUBLIC MANAGEMENT OF THE FINANCIAL AND BUDGETARY CAPACITY OF TERRITORIAL COMMUNITIES IN THE CONTEXT OF DECENTRALIZATION - Maliborskyi, Petro (Public Management and Policy, 2026)
The study is devoted to the problem of the financial capacity of territorial communities as one of the foundations of effective local governance in the context of decentralization. The article identifies the potential of territorial communities' financial capacity to indicate the effectiveness of local government bodies' functioning. It is substantiated that the decentralization reform in Ukraine has had a positive impact on local budgets. There is an increase in income, an increase in the share of own revenues, and a minimization of dependence on state transfers. At the same time, the unevenness of such changes is noted, since the level of financial capacity of communities differs significantly due to the different economic development of regions, investment attractiveness, and the influence of external factors, in particular martial law. This state of affairs highlights the need to improve the budget equalization system and implement an adaptive approach to budget policy. Comparison with other countries has shown that the level of financial decentralization in Ukraine is lower than in most EU countries. That is, there is potential for expanding the financial independence of communities. At the same time, in developed countries, the effectiveness of local finances depends not only on the volume of resources, but also on the quality of management, institutional capacity and active use of digital technologies. The study examined the factors that shape the financial capacity of communities: the structure of income, the quality of budget planning, the level of economic development, investment activity and management efficiency. Correlation analysis confirmed the close relationship between the financial indicators of communities and the general economic condition of the regions. The study substantiates that the synergy of the proposed approaches will contribute to strengthening the financial self-sufficiency of communities, which determines the overall quality of public services and support for sustainable regional development.